Lipidic Profile Changes in Exosomes and Microvesicles Derived From Plasma of Monoclonal Antibody-Treated Psoriatic Patients - Paolino, Giovanni; Buratta, Sandra; Mercuri, Santo R.; Pellegrino, Roberto M.; Urbanelli, Lorena; Emiliani, Carla; Bertuccini, Lucia; Iosi, Francesca; Huber, Veronica; Brianti, Pina; Prezioso, Caterina; Di Nicola, Matteo R.; et al. (Frontiers in Cell and Developmental Biology, 2022)
Psoriasis is a chronic immune-mediated inflammatory skin disorder affecting children and adults. To date no approved biomarkers for diagnosis of this disease and follow up of patients have been translated into clinical practice. Recently, extracellular vesicles (EVs) secreted by all cells and present in almost all biological fluids are playing a crucial role in diagnosis and follow up of several diseases, including psoriasis. Since many psoriatic patients show altered plasma lipid profiles and since EVs have been involved in psoriasis pathogenesis, we studied the phospholipid profile of EVs, both microvesicles (MV) or exosomes (Exo), derived from plasma of psoriatic patients undergoing systemic biological treatment (secukinumab, ustekinumab, adalimumab), in comparison with EVs of untreated patients and healthy donors (HD). EVs were evaluated by immune electronmicroscopy for their morphology and by NanoSight for their amount and dimensions. EV phospholipid profiling was performed by High Resolution Liquid Chromatography-Mass Spectrometry and statistical Partial Least Squares Discriminant Analysis. Our results demonstrated that psoriatic patients showed a higher concentration of both MV and Exo in comparison to EVs from HD. The phospholipid profile of Exo from psoriatic patients showed increased levels of phosphatidylcholine (PC), phosphatidylethanolamine (PE), phosphatidylglycerol and lysoPC compared to Exo from HD. Sphingomyelin (SM) and phosphatidylinositol are the only phospholipid classes whose levels changed in MV. Moreover, the therapy with ustekinumab seemed to revert the PE and PC lipid composition of circulating Exo towards that of HD and it is the only one of the three biological drugs that did not alter SM expression in MV. Therefore, the determination of lipid alterations of circulating EVs could harbor useful information for the diagnosis and drug response in psoriatic patients.